Clinical experience with nanoparticle albumin-bound paclitaxel, a novel taxane anticancer agent, and management of adverse events in females with breast cancer - TAKASHIMA, SEIKI (Oncol Lett, 2015)
Nanoparticle albumin-bound paclitaxel (nab-paclitaxel) is currently approved in Japan for treatment of breast cancer. However, apart from phase I clinical trials, data regarding Japanese patients are scant. In the present study, the efficacy and safety of nab-paclitaxel therapy were retrospectively analyzed in 22 patients with advanced or metastatic breast cancer who were treated at the National Hospital Organization Shikoku Cancer Center between November 2010 and June 2012. The nab-paclitaxel was administered once every three weeks. The median age of the patients was 59 years. The tumors were estrogen-receptor positive and/or progesterone-receptor positive in 63.6% patients. None of the patients had HER2-positive breast cancer. The median number of treatment cycles was six (range, two to 12). Six patients exhibited a partial response; the response rate was 27.3% and the clinical benefit rate was 31.8%. The response rate and clinical benefit rate were higher in patients who received nab-paclitaxel as first- or second-line treatment. The median time to treatment failure was 127 days (range, 27–257). Major adverse events were peripheral neuropathy (59%; Grade 3, 9%), myalgia (59%), rash (45%), and nausea and vomiting (50%). The results suggest that nab-paclitaxel is a well-tolerated and clinically useful anticancer preparation.